Biochemical analysis of nucleosome targeting by Tn5 transposase. Issue 8 (14th August 2019) - Sato, Shoko; Arimura, Yasuhiro; Kujirai, Tomoya; Harada, Akihito; Maehara, Kazumitsu; Nogami, Jumpei; Ohkawa, Yasuyuki; Kurumizaka, Hitoshi
Abstract : Abstract : Tn5 transposase is a bacterial enzyme that integrates a DNA fragment into genomic DNA, and is used as a tool for detecting nucleosome-free regions of genomic DNA in eukaryotes. However, in chromatin, the DNA targeting by Tn5 transposase has remained unclear. In the present study, we reconstituted well-positioned 601 dinucleosomes, in which two nucleosomes are connected with a linker DNA, and studied the DNA integration sites in the dinucleosomes by Tn5 transposase in vitro . We found that Tn5 transposase preferentially targets near the entry–exit DNA regions within the nucleosome. Tn5 transposase minimally cleaved the dinucleosome without a linker DNA, indicating that the linker DNA between two nucleosomes is important for the Tn5 transposase activity. In the presence of a 30 base-pair linker DNA, Tn5 transposase targets the middle of the linker DNA, in addition to the entry–exit sites of the nucleosome. Intriguingly, this Tn5-targeting characteristic is conserved in a dinucleosome substrate with a different DNA sequence from the 601 sequence. Therefore, the Tn5-targeting preference in the nucleosomal templates reported here provides important information for the interpretation of Tn5 transposase-based genomics methods, such as ATAC-seq.